KONSEPTUALISASI INTERNALISASI KEARIFAN LOKAL BANGKA BELITUNG DALAM PEMBELAJARAN DONGENG SASTRA ANAK MELALUI PENGEMBANGAN MULTIMEDIA INTERAKTIF ANIMATION 3D - Yorenza Meifinda; Silvio Juliana Nabela; Nurjanah (Edutainment : Jurnal Ilmu Pendidikan dan Kependidikan, 2025)
Bangka Belitung is a province rich in local wisdom that forms an integral part of Indonesia’s cultural identity, one of which is folklore. However, in educational practice, folklore is often neglected in elementary school learning, resulting in a declining appreciation of local literary heritage among students. Therefore, innovative learning approaches are needed to integrate local folklore into the learning process so that it remains relevant and appealing to future generations. This study aims to develop interactive multimedia based on 3D animation as a learning medium to introduce and preserve local folklore from Bangka Belitung. The use of 3D animation is considered effective because it presents animated visuals accompanied by audio, creating an engaging and meaningful learning experience for students. This research employs the Research and Development (R&D) method using the Four-D model, which consists of the stages of Define, Design, Develop, and Disseminate. Data were collected through interviews, observations, and questionnaires, while data analysis focused on assessing the validity and practicality of the developed product. The study was conducted in Indonesian language learning for fourth-grade elementary school students, particularly on folklore material. The results indicate that the developed 3D animated multimedia is valid and practical, and effectively represents the local wisdom of Bangka Belitung through the folklore entitled Putri Tajuk Malam. This study highlights the importance of integrating local cultural values into education through digital innovation.